EDUCATIONAL METHODS IN HADITH PERSPECTIVE - Syahril Rambe; Erwin Pinayungan Dasopang; Wahdi Sihombing (Proceeding International Seminar of Islamic Studies, 2022)
Learning will be better if the learning subjects experience what (material) they are learning for themselves, so that the knowledge transfer process is not verbal but is individual experience (teacher's experience). Meanwhile, the process of transferring knowledge to objects, to a certain extent, requires operational methods and techniques, so that learning outcomes can be obtained optimally. The time of the Prophet was a short period of knowledge transfer (hadith). This period demands seriousness and prudence from the companions as the first generation of heirs of Islamic teachings and the first recipients of the second source of Islamic law (hadith), because it is in their hands that hadith must be preserved and spread to the next heir simultaneously and continuously. The transmission and dissemination of hadith starts from the Prophet's learning process to his companions so that the Prophet's learning method needs to be studied. Related to this issue, it is necessary to discuss several things: (a) how the development of hadith at the time of the Prophet; (b) what was the state of learning hadith at the time of the Prophet; and (c) how was the Prophet's learning method in the process of spreading hadith to his students (his companions). These questions can be answered in the following ways: (1) Hadiths received by certain Companions (after learning from the Prophet) are disseminated to others. the hadith developed by word of mouth so that it can be passed down to generations after them, even today; (2) The study of hadith was carried out since the beginning of the revelation, namely when the Prophet was still in Mecca, even though it was only focused on a few places. (3) The Prophet's learning is carried out through gradual stages, in an elegant, varied manner, through example in practical life. That is, the Prophet's learning is not limited to people with a certain level, a certain age and a certain gender, because the Prophet's job is to provide enlightenment for all people.Keywords: Educational, Methods, Hadith